What accounts for the German Labor Market Miracle? A Macroeconomic Investigation - Stefan Schiman; Mathias Klein (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
We study the driving forces of the so-called "German labor market miracle" the trend-shift and steady decline of German unemployment over the last two decades that persisted beyond the Great Recession. Our structural VAR approach encompasses various factors within a single comprehensive framework based on robust sign restrictions. We find that wage bargaining shocks account for most of the observed unemployment decline. Wage moderation was most pronounced right after the implementation of Hartz IV, but it persisted far beyond that. Moreover, the real effects of wage bargaining shocks were stronger post-1999, i.e. within the monetary union. In contrast, the muted response of unemployment to the Great Recession was not significantly different to the experience in previous business cycle downturns. The results are robust to several modifications of the model and changes in the sample.
Keywords: C32; E24; E32; 330; German labor market miracle; structural VAR; sign restrictions